A critical landscape and urban design analysis of Egypt's new Administrative Capital City. Issue 1 (2nd January 2021) - Bolleter, Julian; Cameron, Robert
Abstract: The Egyptian government has touted the new Administrative Capital City near Cairo as a flagship for 'Smart City' developments across Africa. Despite its association with the UN Sustainable Development Goals, critics argue that the project will be highly detrimental to existing cities, their inhabitants and the natural environment. Using a normative framework derived from the UN goals, this paper examines whether the design of Phase One of the Administrative Capital City (2015–2020) delivers on its grand narratives and commitments. It reveals that the project fails to meet many of its aspirations and is likely to compound Egypt's water supply issues, conflict with fragile desert environments, be vehicular-dependent, isolate everyday Cairenes from Egypt's governance institutions and entrench the power of an autocratic leader. As such, the new capital presents a problematic model of urban development for dealing with Cairo's environmental and societal issues, and for broadly accommodating Africa's rapidly urbanizing population.